2020
DOI: 10.14428/nemesis.v14i1.59953
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dental private practitioners to publications on anatomical variations using cone beam computed tomography

Abstract: Objective: To investigate the participation of citizens-dental private practitioner in scientific articles about anatomical variations on dentomaxillofacial CBCT. Our null hypothesis was that private practice practitioners are not involved in publications on anatomical variations using cone beam computed tomography. Material and methods: This study was performed from home without access to our university library. Only PubMed database was used to perform our study. We found 384 articles published among 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The quantitative measurements also provide evidence for some anatomical landmarks such as complexity of canal morphology (Figure 33), suitability for post-placement procedures in double-rooted maxillary premolars and angles for root canal curvatures. However, one study found that only 3% of CBCT clinical studies related to anatomical variations in the oral and maxillofacial region were contributed by private practitioners, which was explained by lack of interest, insufficient training and limited access to CBCT data (Hebda et al, 2020). The involvement of CBCT data from private dental practitioners and endodontic specialists can be one important way for clinical translation in which research findings can be correlated with problems encountered in daily practice especially since the data obtained from private practice will be mainly from complicated clinical cases related to restorative dentistry, which is not the usual CBCT data profile gained from university hospitals/ etc., where cases are usually related to trauma, orthodontic treatment, oral and maxillofacial surgery (in addition to restorative dentistry).…”
Section: Translation Of Root and Canal Anatomy Studies To Clinical Pr...mentioning
confidence: 99%
“…The quantitative measurements also provide evidence for some anatomical landmarks such as complexity of canal morphology (Figure 33), suitability for post-placement procedures in double-rooted maxillary premolars and angles for root canal curvatures. However, one study found that only 3% of CBCT clinical studies related to anatomical variations in the oral and maxillofacial region were contributed by private practitioners, which was explained by lack of interest, insufficient training and limited access to CBCT data (Hebda et al, 2020). The involvement of CBCT data from private dental practitioners and endodontic specialists can be one important way for clinical translation in which research findings can be correlated with problems encountered in daily practice especially since the data obtained from private practice will be mainly from complicated clinical cases related to restorative dentistry, which is not the usual CBCT data profile gained from university hospitals/ etc., where cases are usually related to trauma, orthodontic treatment, oral and maxillofacial surgery (in addition to restorative dentistry).…”
Section: Translation Of Root and Canal Anatomy Studies To Clinical Pr...mentioning
confidence: 99%